Impact of respiratory therapy in vital capacity and functionality of patients undergoing abdominal surgery - Shanlley Cristina da Silva Fernandes; Rafaella Souza dos Santos; Erica Albanez Giovanetti; Corinne Taniguchi; Cilene Saghabi de Medeiros Silva; Raquel Afonso Caserta Eid; Karina Tavares Timenetsky; Denise Carnieli-Cazati (Einstein (São Paulo))
ABSTRACT Objective To evaluate the vital capacity after two chest therapy techniques in patients undergoing abdominal surgical. Methods A prospective randomized study carried out with patients admitted to the Intensive Care Unit after abdominal surgery. We checked vital capacity, muscular strength using the Medical Research Council scale, and functionality with the Functional Independence Measure the first time the patient was breathing spontaneously (D1), and also upon discharge from the Intensive Care Unit (Ddis). Between D1 and Ddis, respiratory therapy was carried out according to the randomized group. Results We included 38 patients, 20 randomized to Positive Intermittent Pressure Group and 18 to Volumetric Incentive Spirometer Group. There was no significant gain related to vital capacity of D1 and Ddis of Positive Intermittent Pressure Group (mean 1,410mL±547.2 versus 1,809mL±692.3; p=0.979), as in the Volumetric Incentive Spirometer Group (1,408.3mL±419.1 versus 1,838.8mL±621.3; p=0.889). We observed a significant improvement in vital capacity in D1 (p<0.001) and Ddis (p<0.001) and in the Functional Independence Measure (p<0.001) after respiratory therapy. The vital capacity improvement was not associated with gain of muscle strength. Conclusion Chest therapy, with positive pressure and volumetric incentive spirometer, was effective in improving vital capacity of patients submitted to abdominal surgery.